Automated analysis of microstructural effects on the failure response of heterogeneous adhesives. (1st March 2016) - Soghrati, Soheil; Liang, Bowen
Abstract: Adhesive bonding enables the joining of thin and dissimilar materials, which is one of the main requirements for manufacturing lightweight structures in the automotive and aerospace industries. However, due to the small thickness and complex microstructure of the adhesive layer, which is often reinforced with embedded heterogeneities to improve its mechanical behavior, simulating the damage process in the adhesive can be a challenging task. In this work, we implement a computational cohesive model to quantify the effects of microstructural features such as particles volume fraction, pre-existing flaws, and surface roughness of adherends on the failure response of a heterogeneous adhesive with embedded glass particles. The hierarchical interface-enriched finite element method (HIFEM) is implemented as the main computational engine for simulating the initiation and propagation of damage in the adhesive layer. This mesh-independent method allows for using finite element meshes that are completely independent of the problem morphology, which considerably facilitates conducting multiple damage simulations for adhesive models with different microstructural features. We also introduce a new virtual prototyping algorithm and integrate that with the HIFEM to enable the automated construction of realistic models of the adhesive microstructure based on digital data.